Pregnancy intendedness in a high-risk obstetric population in a regional hospital - Akpakan, Akanimo (Department of Obstetrics and Gynaecology, 2024)
Unintended pregnancies (UIP) are those that are mistimed, unplanned, or unwanted at the time of conception. It is estimated that, worldwide, 40% of pregnancies were unplanned in 2012 and this carries increased risks for both mothers and babies. This study was designed to utilise the London Measure of Unplanned Pregnancy (LMUP) to assess pregnancy intendedness in a high-risk obstetric population of women who were accessing care at a large regional hospital. Methods: This was a cross-sectional descriptive study. Women attending the High-Risk clinics or admitted with medical problems were recruited at George Regional Hospital. Once they consented to the study, the LMUP was administered by a single research team member. The LMUP is a psychometrically validated measure of pregnancy intention for a current or recent pregnancy. Questions enquire about the intention and timing of pregnancy, preconception behaviour, contraception usage, and partner's input and a score is obtained which indicates intendedness. It has been validated in our department in the 3 local languages. Results: A total of 200 women were recruited for the study. No potential participant declined to be interviewed. The mean age was 30.4+/- 6.3 years and the majority of participants were of mixed ancestry (n=135). HIV status was positive for 23 participants and unknown for 29. All participants completed the Perinatal Mental Health Score and 4 required referrals for supportive assistance. The LMUP indicated that 76 women had unintended pregnancies, 58 were ambivalent about their pregnancies and 66 had an intended pregnancy. Pre-pregnancy discussion and preparation were lacking for most of the participants despite pre-existing risk factors. Pregnancy intendedness was affected by several factors. Age (P = 0.02), relationship status (P = 0.001) and financial support (P = 0.005) were associated with intendedness. Employment, parity, language group, educational level, booking gestation, HIV status, and multiple comorbidities did not affect pregnancy intendedness. Other factors that had no influence were Perinatal Mental Health Score, preconceptual counselling/health improvement, and habits. Poor partner communication was common. Women at extremes of reproductive life had more unplanned pregnancies (P = 0.02). i There was good unprompted contraceptive knowledge but poor information about emergency contraception. Conclusion: In this high-risk group of obstetric patients, there was little preconception discussion or preparation and inadequate use of contraception among women who did not plan a pregnancy.